2021
DOI: 10.1111/adb.13071
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a novel biological mechanism for alcohol addiction associated with circRNA networks acting as potential miRNA sponges

Abstract: Our lab and others have shown that chronic alcohol use leads to gene and miRNA expression changes across the mesocorticolimbic (MCL) system. Circular RNAs (circRNAs) are noncoding RNAs that form closed‐loop structures and are reported to alter gene expression through miRNA sequestration, thus providing a potentially novel neurobiological mechanism for the development of alcohol dependence (AD). Genome‐wide expression of circRNA was assessed in the nucleus accumbens (NAc) from 32 AD‐matched cases/controls. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 103 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…This may be due to differences in treatment regimens and brain region. A study on postmortem nucleus accumbens tissue from patients with alcohol use disorder identified networks of predicted circRNA-microRNA-mRNA interactions that are regulated with chronic alcohol use [57]. Intrathecal injection of the opioid morphine regulated expression of circRNAs in the spinal cord [58] and systemic treatment with morphine regulated expression of circRNAs arising from the mu-opioid receptor in the whole brain of mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in treatment regimens and brain region. A study on postmortem nucleus accumbens tissue from patients with alcohol use disorder identified networks of predicted circRNA-microRNA-mRNA interactions that are regulated with chronic alcohol use [57]. Intrathecal injection of the opioid morphine regulated expression of circRNAs in the spinal cord [58] and systemic treatment with morphine regulated expression of circRNAs arising from the mu-opioid receptor in the whole brain of mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown or overexpression of circRNAs has an impact on the occurrence and development of cancer cells. There are various mechanisms for the regulation of circRNAs on tumors, such as: miRNA sponges [23], interaction with proteins [24], etc. One of the most common regulatory mechanisms is the circRNAs as endogenous competitive RNAs [25].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown or overexpression of circRNAs has an impact on the occurrence and development of cancer cells. There are various mechanisms for the regulation of circRNAs on tumors, such as miRNA sponges [ 23 ] and interaction with proteins [ 24 ]. One of the most common regulatory mechanisms is the circRNAs as endogenous competitive RNAs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%